Sistem Pengendalian Internal Piutang pada Karyawan Outsourcing di PT. Swabina Gatra - Yuliani, Kartika Putri; Wasti Reviandani (MES Management Journal, 2024)
Delays in issuing invoices are a significant problem that can affect the efficiency of a company's administration and financial management. This research aims to identify the causes of invoice delays and evaluate the processes and documents related to their issuance. This research uses a qualitative approach with interview techniques. The research results show that internal factors such as lack of coordination between departments and external factors such as delays in sending documents by third parties are the main causes of invoice delays. Apart from that, the SOP for issuing invoices that is not optimal also contributes to this problem. The process of paying receivables takes varying amounts of time, depending on the accuracy of submitting invoice documents. In conclusion, improving internal coordination, document management, and better implementation of SOP can increase the efficiency of the billing process. These findings provide a practical contribution in supporting more effective corporate financial management.